2001
DOI: 10.1086/323906
|View full text |Cite
|
Sign up to set email alerts
|

Iron Kα Emission from X-Ray Reflection: Predictions for Gamma-Ray Burst Models

Abstract: Recent observations of several g-ray burst (GRB) afterglows have shown evidence for a large amount of X-ray line-emitting material, possibly arising from ionized iron. A significant detection of an X-ray spectral feature, such as that found in the Chandra observation of GRB 991216, may provide important constraints on the immediate environment of the burst and hence on progenitor models. The large Fe Ka equivalent widths inferred from the X-ray observations favor models in which the line is produced when the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 19 publications
2
47
0
Order By: Relevance
“…In the ''nearby reprocessor'' scenario, a long-lived central engine (Rees & Mészáros 2000) or a plasma bubble GRB (Mészáros & Rees 2001) ionizes material on the sides of a funnel carved out of the progenitor star by the GRB (at R $ 10 13 cm). Ballantyne & Ramirez-Ruiz (2001) study the equivalent widths of Fe lines, for each scenario, as a function of the continuum luminosity. Roughly, they find that the equivalent widths peak near 1 keV in each scenario for solar abundances and incident X-ray continuum luminosities of order 10 46 ergs s À1 .…”
Section: Comparison With Theoretical Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ''nearby reprocessor'' scenario, a long-lived central engine (Rees & Mészáros 2000) or a plasma bubble GRB (Mészáros & Rees 2001) ionizes material on the sides of a funnel carved out of the progenitor star by the GRB (at R $ 10 13 cm). Ballantyne & Ramirez-Ruiz (2001) study the equivalent widths of Fe lines, for each scenario, as a function of the continuum luminosity. Roughly, they find that the equivalent widths peak near 1 keV in each scenario for solar abundances and incident X-ray continuum luminosities of order 10 46 ergs s À1 .…”
Section: Comparison With Theoretical Predictionsmentioning
confidence: 99%
“…Claims of low-to moderatesignificance emission lines have been made on the basis of data from several missions: Fe lines have been detected in afterglow data from ASCA (Advanced Satellite for Cosmology and Astrophysics; Yoshida et al 1999), BeppoSAX ( Piro et al 1999;Antonelli et al 2000), and the Chandra X-Ray Observatory (Piro et al 2000); and lines from highly ionized light, multiple-elements such as Mg, Si, S, Ar, and Ca have been detected in afterglow data from XMM-Newton (Reeves et al 2002;Watson et al 2003) and Chandra (Butler et al 2003). The detections are challenging to theorists because they typically imply large, concentrated masses of metals in the circumburst material (see, e.g., Lazzati et al 1999) and a very efficient reprocessing of the nonthermal afterglow continuum into line radiation (see Ballantyne & Ramirez-Ruiz 2001;Lazzati et al 2002). For observers, the challenge is to obtain significant and unambiguous detections or firm upper limits.…”
Section: Introductionmentioning
confidence: 99%
“…We find that iron enrichment is not necessary to reproduce the line strength, although if the true ionization parameter is substantially different than the best-fit value ξ ≈ 10 3 , then a moderately super-solar abundance will help bring the line to the required power (Ballantyne & Ramirez-Ruiz 2001;Ballantyne et al 2002). In addition, even if at a non-statistically significant level, the model seems to underestimate the line strength in the grating spectrum, and a supersolar metallicity may cure this.…”
Section: Discussionmentioning
confidence: 74%
“…Ballantyne & Ramirez-Ruiz 2001). Low values of the ionization parameter (ξ < 100) will produce a reflection component with evident lines.…”
Section: Discussionmentioning
confidence: 99%
“…Woosley & Weaver 1995). Reeves et al (2003) also considered the possibility that the spectrum is produced through the reflection by an ionized slab (Ross & Fabian 1993;Ballantyne & Ramirez-Ruiz 2001), but concluded that this model (either "pure" or with an underlying power-law) cannot reproduce the data. However (as explicitly noted by the authors), most of the discrepancy between the model and the data is localized in the region around 1 keV, where lines from elements not included in the ionized reflection model, such as S, Ar and Ca, are expected.…”
Section: Introductionmentioning
confidence: 99%